Bacterial bio-cementation can repair space bricks - Gupta, Nitin; Kulkarni, Rohan; Naik, Arya R.; Viswanathan, Koushik; Kumar, Aloke (Frontiers in Space Technologies, 2025)
This study investigates the potential of Microbially Induced Calcium Carbonate Precipitation (MICP) as a repair technique for consolidated (sintered) bricks made from Lunar Highland Simulant-1 (LHS-1), aiming to extend their functional lifespan in extra-terrestrial conditions. Sintered bricks (compressive strength ∼50 MPa) were fabricated with embedded holes, V-shaped notches, and semi-circular notches to simulate structural failure. The compressive strength of these modified bricks was assessed, revealing a significant reduction in strength due to stress concentrations around these cavities. Following this, the cavities were filled with a MICP-based soil slurry, resulting in a notable recovery of compressive strength (∼28%–54%), although not to the levels of the original material. Scanning electron microscopy (SEM) analysis demonstrated strong interfacial bonding between the MICP filler and the sintered substrate, indicating the effectiveness of the repair method. Additionally, Digital Image Correlation (DIC) was used to track the crack propagation and growth under the loading conditions. Instances of crack propagation through the MICP interface highlight areas for further investigation. The findings underscore the viability of MICP as a sustainable solution for repairing construction materials, aligning with contemporary practices aimed at enhancing durability and reducing dependency on Earth.